+0

# solve the system of equations using elimination

+3
293
1
+4

6x-8y=-64

5x-8y=-60

jeezdude  Apr 21, 2015

#2
+80987
+5

6x-8y=-64   (1)

5x-8y=-60   (2)

Subtract equation 2 from 1  ....  so we have....

x = -4               and substituting this into the first equation to find y, we have

6(-4) - 8y = - 64

-24 - 8y = -64      add 24 to both sides

-8y  = - 40   divide both sides by -8

y = -40/-8 = 5

So....the solution is (x,y) = (-4, 5)

CPhill  Apr 21, 2015
Sort:

#2
+80987
+5

6x-8y=-64   (1)

5x-8y=-60   (2)

Subtract equation 2 from 1  ....  so we have....

x = -4               and substituting this into the first equation to find y, we have

6(-4) - 8y = - 64

-24 - 8y = -64      add 24 to both sides

-8y  = - 40   divide both sides by -8

y = -40/-8 = 5

So....the solution is (x,y) = (-4, 5)

CPhill  Apr 21, 2015

### 15 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details